1999
DOI: 10.1136/pgmj.75.879.13
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in enzymatic antioxidant defence in diabetes mellitus − a rational approach

Abstract: SummaryDefence against the reactive oxidants produced during aerobic metabolism is a complex process and is provided by a system of enzymes and antioxidant compounds capable of preventing excess radical production, neutralising free radicals and repairing the damage caused by them. Regulation of the antioxidant system must provide suYcient, properly located, antioxidant compounds and enzymes. Damage to this system has been proved to play a role in various disorders. Long-term complications of diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 38 publications
(44 reference statements)
3
50
1
5
Order By: Relevance
“…Results of other studies concerning GPx activity in HT subjects are contradictory showing both increased and decreased activity of the enzyme [23]. The same conclusion can be made regarding review of diabetes mellitus studies [ 24,25]. Although GPx1 remained unchanged, GR activity increased significantly in HT group.…”
Section: Discussionsupporting
confidence: 62%
“…Results of other studies concerning GPx activity in HT subjects are contradictory showing both increased and decreased activity of the enzyme [23]. The same conclusion can be made regarding review of diabetes mellitus studies [ 24,25]. Although GPx1 remained unchanged, GR activity increased significantly in HT group.…”
Section: Discussionsupporting
confidence: 62%
“…Intracellular antioxidative defense is primarily enabled by the antioxidative enzymes, most significant of which are SOD, CAT and GSH-Px (Andrea et al,2004;Maritim et al, 2003;Szaleczky et al, 1999;. These three antioxidant enzymes differ in their structure, tissue distribution and cofactors required for functioning.…”
Section: Antioxidant Protectionmentioning
confidence: 99%
“…Previous studies (8,9) have suggested that diabetic patients are under a state of oxidative stress characterized by a relative overload of oxidants. In these patients, free oxygen radicals, especially superoxide (O 2 -), are aberrantly accumulated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Such coordination is largely dependent on the nitric oxide (NO) released from nerve endings of parasympathetic nerves, which serves as a major neurotransmitter (5,6). NO can diffuse into the smooth musculature of the urethra, in which it stimulates the synthesis of cyclic guanosine monophosphate (cGMP) and finally induces smooth muscle cell relaxation (7).Previous studies (8,9) …”
mentioning
confidence: 99%